Cladistic analysis and biogeography of Brachystethus Laporte (Heteroptera, Pentatomidae, Edessinae) - Barcellos, Aline; Grazia, Jocélia (Zootaxa, 2003)
In this paper, Brachystethus Laporte, 1832 is analyzed cladistically, using 21 characters and 15 taxa, including as outgroups, in a first analysis, the genera Neotibilis Grazia & Barcellos, 1994, Edessa Fabricius, 1803, Olbia Stål, 1862, Peromatus Amyot & Serville, 1843, and Pantochlora Stål, 1870. Further, these edessine genera were included in the ingroup, without any changes in the only resulting cladogram. The monophyly of Brachystethus is supported by four synapomorphies: metasternal carina partially bifurcated, pygophore with blade-like processes, anterior margin of gonocoxites 9 deeply concave medially, and a mesial thickening on gonapophyses 9. Brachystethus shares with Edessa, Olbia, Pantochlora, and Peromatus four synapomorphies: loss of subcallous margin on pronotum, mesosternal carina lower than metasternal carina, phallus with a short vesica, and presence of a beak-like projection on the thickening of vaginal intima. Based on the cladogram, the transferal of Brachystethus to Edessinae is here proposed. Biogeographical analysis has shown congruence between the distributional pattern of the clade formed by B. rubromaculatus Dallas, 1851, B. signoreti Stål, 1872, B. cribrus (Fabricius, 1781), and Brachystethus sp. nov. A, and vicariant events on Neotropical region, in the late Cretaceous.